Assessment of affective dysregulation in children: development and evaluation of a semi-structured interview for parents and for children - Treier, Anne-Katrin; Labarga, Sara Zaplana; Ginsberg, Claudia; Kohl, Lea Teresa; Görtz-Dorten, Anja; Ravens-Sieberer, Ulrike; Kaman, Anne; Banaschewski, Tobias; Aggensteiner, Pascal; Hanisch, Charlotte; Kölch, Michael; Daunke, Andrea; et al. (Child and adolescent psychiatry and mental health, 2024)
Children with affective dysregulation (AD) show an excessive reactivity to emotionally positive or negative stimuli, typically manifesting in chronic irritability, severe temper tantrums, and sudden mood swings. AD shows a large overlap with externalizing and internalizing disorders. Given its transdiagnostic nature, AD cannot be reliably and validly captured only by diagnostic categories such as disruptive mood dysregulation disorder (DMDD). Therefore, this study aimed to evaluate two semi-structured clinical interviews—one for parents and one for children. Both interviews were developed based on existing measures that capture particular aspects of AD. We analyzed internal consistencies and interrater agreement to evaluate their reliability. Furthermore, we analyzed factor loadings in an exploratory factor analysis, differences in interview scores between children with and without co-occurring internalizing and externalizing disorders, and associations with other measures of AD and of AD-related constructs. The evaluation was performed in a screened community sample of children aged 8-12 years (n = 445). Interrater reliability was additionally analyzed in an outpatient sample of children aged 8-12 years (n = 27). Overall, internal consistency was acceptable to good. In both samples, we found moderate to excellent interrater reliability on a dimensional level. Interrater agreement for the dichotomous diagnosis DMDD was substantial to perfect. In the exploratory factor analysis, almost all factor loadings were acceptable. Children with a diagnosis of disruptive disorder, attention-deficit/hyperactivity disorder, or any disorder (disruptive disorder, attention-deficit/hyperactivity disorder, and depressive disorder) showed higher scores on the DADYS interviews than children without these disorders. The correlation analyses revealed the strongest associations with other measures of AD and measures of AD-specific functional impairment. Moreover, we found moderate to very large associations with internalizing and externalizing symptoms and moderate to large associations with emotion regulation strategies and health-related quality of life. The analyses of internal consistency and interrater agreement support the reliability of both clinical interviews. Furthermore, exploratory factor analysis, discriminant analyses, and correlation analyses support the interviews’ factorial, discriminant, concurrent, convergent, and divergent validity. The interviews might thus contribute to the reliable and valid identification of children with AD and the assessment of treatment responses. ADOPT Online: German Clinical Trials Register (DRKS) DRKS00014963. Registered 27 June 2018.
Gesehen am 15.01.2025